Pengaruh Fasilitas Wisata dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Hidden Strawberry Garden di Desa Pancasari - Siadi, Ni Made Astiti Putri; Sudarma, I Made; Ustriyana, I Nyoman Gede (Nandur; Vol 2 No 2 (2022), 2022)
The existence of agro-tourism in several areas has become one of the sectors that can provide benefits for increasing income. Pancasari Village is one of the villages that has the potential for agricultural land and agricultural crops that have the potential to develop agro-tourism-based destinations. For example, strawberry agrotourism at Hidden Strawberry Garden. This research aims to explain the influence that provided by tourist facilities and service quality on visitor satisfaction. The type of research used is quantitative by looking for causal associative relationships with sampling using non-probability sampling method with accidental sampling with a sample of 120 respondents which are visitors of Hidden Strawberry Garden. The data analysis technique used Structural Equation Least Square (SEM-PLS) analysis. The results of this study conclude that the tourist facilities variable has a significant influence on visitor satisfaction. The influential indicator is the condition of the facility and the quality of service has a significant influence on visitor satisfaction. The indicator that influences is the condition of the facility. The advice given as an evaluation is that the manager is able to monitor more by improving the supporting facilities and infrastructure on a regular basis and being able to improve the quality of skills in providing services so as to increase visitor and satisfaction and loyalty.